EFFECTIVENESS OF BETEL AND KIRINYUH LEAF EXTRACTS TESTED IN VIVO AGAINST SCABIES IN GOATS - Aulyani, Tutik Lusyta; Hasim, Nazra Risalah; Nuraeni, Nuraeni; Juwita, Sartika; Andy, Andy; Wahyuni, Sri (Buletin Veteriner Udayana, 2023)
The aim of this study is to test the effectiveness of in vivo herbal sprays of kirinyuh and betel leaves against scabies in goats. Samples were divided into 5 treatment groups. The treatment variable in this study were, one negative control or no treatment, one positive control group with kudix, one group with 30% kirinyuh leaf extract, one group with 30% betel leaf extract, and one group with kirinyuh and betel leaf extracts with respective concentrations of 15%. While the parameters observed are; extensive alopecia, skin thickening and scalded. Treatment was given by spraying evenly on the entire surface of the scabies wound 2 times a day and then observing on the 14th day. The results showed that 30% kirinyuh leaf extract had the best scabies healing effect compared to other treatments. The parameter that shows the best healing is the scab area parameter. This is due to the content of flavonoids, saponins, and tannins which have the effect of helping scabies wound healing. It is necessary to carry out further research on other factors that can affect the healing rate of scabies wounds given treatment such as environmental factors and feed